Modelling plasma response to RMP fields in ASDEX Upgrade with varying edge safety factor and triangularity. (8th September 2016) - Li, L.; Liu, Y.Q.; Kirk, A.; Wang, N.; Liang, Y.; Ryan, D.; Suttrop, W.; Dunne, M.; Fischer, R.; Fuchs, J.C.; Kurzan, B.; Piovesan, P.; et al.
Abstract: Toroidal computations are performed using the MARS-F code (Liu et al 2000 Phys. Plasmas 7 3681), in order to understand correlations between the plasma response and the observed mitigation of the edge localized modes (ELM) using resonant magnetic perturbation fields in ASDEX Upgrade. In particular, systematic numerical scans of the edge safety factor reveal that the amplitude of the resonant poloidal harmonic of the response radial magnetic field near the plasma edge, as well as the plasma radial displacement near the X -point, can serve as good indicators for predicting the optimal toroidal phasing between the upper and lower rows of coils in ASDEX Upgrade. The optimal coil phasing scales roughly linearly with the edge safety factor q 95, for various choices of the toroidal mode number n   =  1–4 of the coil configuration. The optimal coil phasing is also predicted to vary with the upper triangularity of the plasma shape in ASDEX Upgrade. Furthermore, multiple resonance effects of the plasma response, with continuously varying q 95, are computationally observed and investigated.